2014
DOI: 10.4172/2167-1168.1000162
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Health Locus of Control, Psychosocial Status and Glycemic Control in Type 2 Diabetes Adults

Abstract: Background: Although a common thread among diabetic behavior is the importance of perceived glycemic control, little is known of the factors that lead to psychosocial status in this population. Purpose: We determine whether the psychosocial factors of health locus of control, self-efficacy, self-care behavior, and depression relate to glycemic control in type 2 diabetes. Method: We used a descriptive correlational design. In total, 285 subjects were enrolled from diabetic outpatient clinics in Southern Taiwan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
3
0
4
Order By: Relevance
“…Çalışmalarda, diyabeti olan bireylerin genellikle iç kontrol ve güçlü başkaları kontrol odaklarının yüksek olduğu gözlemlenmiştir. 14,21 Ülkemizde ise diyabet hastalarının kontrol algılarına yönelik sınırlı sayıda çalışmaya ulaşılmıştır. Bireylerin, iç kontrol odaklarının güçlü başkaları kontrol odağına yakın olması bireylerin hastalık algısının yüksek olmasıyla açıklanabilir.…”
Section: Güçlü Başkaları Kontrol Odağındaunclassified
See 3 more Smart Citations
“…Çalışmalarda, diyabeti olan bireylerin genellikle iç kontrol ve güçlü başkaları kontrol odaklarının yüksek olduğu gözlemlenmiştir. 14,21 Ülkemizde ise diyabet hastalarının kontrol algılarına yönelik sınırlı sayıda çalışmaya ulaşılmıştır. Bireylerin, iç kontrol odaklarının güçlü başkaları kontrol odağına yakın olması bireylerin hastalık algısının yüksek olmasıyla açıklanabilir.…”
Section: Güçlü Başkaları Kontrol Odağındaunclassified
“…10 Diyabette sağlık kontrol odakları ile ilgili çalışmalarda, iç kontrol odağına sahip bireylerde düzenli diyet ve egzersiz oranlarının yüksek olduğu, 12,13 iç kontrol odağının HbA1c düzeyi ile ilişkili 11 öz-etkililik ve öz bakım davranışlarıyla pozitif bir etkileşim içerisinde olduğu görülmüştür. 14 Ülkemizde, sağlık kontrol odağı algısı üzerinde yapılan araştırmalar incelendiğinde, genellikle eğitim bilimleri ve psikoloji gibi alanlarda yapıldığı, sağlıkla ilgili olarak diyabet alanında ise sınırlı sayıda 3 , araştırmanın olduğu görülmüştür. Sağlık kontrol odakları, çeşitli durumlardan ve faktörlerden etkilenebilmektedir.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…In diabetics, changes in HLOC may precede changes in self-care behaviors. In fact, several previous studies have shown that type 2 diabetic with internal HLOC showed better diabetic diet adaptation, better adherence to self-care behaviors, and better glycemic control [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%